Malaysian Public’s Perception Toward Event Data Recorder (EDR) in Vehicles - Fadhlan Hafizhelmi Kamaru Kamaru Zaman; Ismail Danish Rozaimi; Syahrul Afzal Che Abdullah; Lucyantie Mazalan; Husna Zainol Abidin; Amir Radzi Ab. Ghani; Yahaya Ahmad (Automotive Experiences)
The Event Data Recorder (EDR) is an important device in a vehicle that can be used to analyze vehicle accidents. EDRs record and store crucial sensor data before, during, and after accidents, which can be used in reconstructing accident events. EDR has been regulated in the US and UK; however, its implementation in the ASEAN region, especially in Malaysia, is relatively new. In this study, a survey is conducted to investigate the perception of Malaysians toward EDR. There are three focuses of this survey: (1) the public's awareness of EDR's existence; (2) their perception of the benefits of EDR; and (3) their privacy concerns with the use of EDR in vehicles. The survey revealed that a majority (75.4%) of respondents were unaware of the existence of EDR, but 72.3% acknowledged that EDR could help identify accident causes, and 59.5% believed it could promote safer driving. Moreover, over 66% of respondents agreed that EDR could enhance vehicle and road safety. Besides, 40.3% expressed concern about potential privacy breaches and misuse of EDR data. Despite that, nearly 80% of respondents were in favor of installing EDR in their vehicles and allowing the data to be used in court. Additionally, 70% indicated that EDR would become a criterion for vehicle selection, and they would support mandatory EDR regulations.